2023
DOI: 10.1007/s10903-023-01453-w
|View full text |Cite
|
Sign up to set email alerts
|

Strategies Used by Healthcare Systems to Communicate with Hospitalized Patients and Families with Limited English Proficiency During the COVID-19 Pandemic: A Narrative Review

Abstract: The COVID-19 pandemic disproportionately affected racial and ethnic minorities in the United States, including many with limited English proficiency (LEP). These patients face various communication barriers, including a shortage of available interpreters and the need for masks that exacerbated communication barriers. It is not known how hospitals responded to these unique challenges to providing language services for the large number of patients with LEP during COVID-19. This narrative review assessed literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Anecdotal evidence as well as work we have conducted has demonstrated that the COVID-19 caused a paradigm shift in how interpreter and language services have been provided to patients over the last three years. 93 , 94 While it is true that many institutions always relied exclusively on remote phone and video interpretation, institutions that had integrated in-person interpreters into the clinical practice, almost completely switched to remote interpretation. 93 , 94 With high staff turnover during the pandemic years many staff have only ever used remote video interpretation, and some are not even aware of the presence of in-person interpreters in the institution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anecdotal evidence as well as work we have conducted has demonstrated that the COVID-19 caused a paradigm shift in how interpreter and language services have been provided to patients over the last three years. 93 , 94 While it is true that many institutions always relied exclusively on remote phone and video interpretation, institutions that had integrated in-person interpreters into the clinical practice, almost completely switched to remote interpretation. 93 , 94 With high staff turnover during the pandemic years many staff have only ever used remote video interpretation, and some are not even aware of the presence of in-person interpreters in the institution.…”
Section: Discussionmentioning
confidence: 99%
“… 93 , 94 While it is true that many institutions always relied exclusively on remote phone and video interpretation, institutions that had integrated in-person interpreters into the clinical practice, almost completely switched to remote interpretation. 93 , 94 With high staff turnover during the pandemic years many staff have only ever used remote video interpretation, and some are not even aware of the presence of in-person interpreters in the institution. Furthermore, even among those who are aware of these services and previously used them and vouch for the importance and benefits of in-person interpreters, the usability and immediacy of the video has made it challenging to change clinician behavior to re-adopt in-person interpreters after pandemic safety measures have been discontinued.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the pandemic led to a decrease in PMI utilization [53]. However, while in-person interpreting appointments decreased, PMIs noticed more remote interpreting appointments and the need to adopt remote communication techniques [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported decreases, while others reported increases in PMI use [53,54]. While in-person interpreting appointments halted, new opportunities emerged, including the incorporation of novel approaches and a transition toward more remote interpreting [54][55][56].…”
Section: Role Of Professional Medical Interpretersmentioning
confidence: 99%